The Adventurous Verse of Emma Gamboa: Poet, Children´s Poetry by the Teacher, Pedagogue and Writer - Rubio Torres, Carlos (2021)
This essay is a reflection on the poetry of Emma Gamboa Alvarado (1901-1976), with a specific emphasis on children´s poetry. It also explores literary texts that influences her work, most written by Costa Ricans, such as Omar Dengo, Joaquín García Monge, Roberto Brenes Mesén and Carmen Lyra. The  foreign voices of José Martí, Gabriela Mistral, Claudia Lars, Rabindranath Tagore and Walt Whitman were also influential. As a result, Gamboa proposed the idea of the democratization of reading while organizing the First Costa Rican Book in 1954. Literary articles and interviews regarding the author´s poetry were also used and contrasted with theoretical positions of her time as well as the present day. A recommendation is made to reprint the work of this author to foster knowledge of her poetry, particulary that aimed at children.